The role of the Commitment Maker Officer (PPK) in anticipating failures in the Village Tanjung Jaya - MMC District IPUH Road Improvement Project (HOTMIX) - Yusuf, Muhammad; Kamil, Insannul (International Journal of Education, Information Technology, and Others, 2024)
This research explores the role of the Commitment Maker Officer in managing the hotmix road improvement project in Tanjung Jaya Village – Ipuh Subdistrict, MMC. The research findings indicate that risk awareness, effective coordination, and preventive actions by the Commitment Maker Officer play a crucial role in anticipating and addressing potential project failures. Risk factors, such as design changes and utility relocation, are well-managed through effective communication and the implementation of addendums. Contractor performance evaluation and project progress monitoring are critical steps taken by the Commitment Maker Officer to ensure that the project proceeds according to plan. The results of this research provide a deep understanding of the strategic role of the Commitment Maker Officer in maintaining the smooth progress of construction projects. In conclusion, a combination of good risk awareness, effective coordination, and appropriate preventive actions make the Commitment Maker Officer a determining factor in the success of hotmix road improvement projects.